2017
DOI: 10.19173/irrodl.v18i4.3032
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of College Faculty Who Use OER

Abstract: Research indicates that students find open educational resources (OER) favorable, but there is no research regarding students' perceptions of faculty who use open textbooks. In the present study we examined this topic experimentally with two undergraduate psychology courses at a small public university. Participants read two passages-one about an instructor using an open textbook and another using a traditional copyrighted textbook-and rated each instructor on a range of characteristics throughclosed-and open-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
0
14
1
Order By: Relevance
“…In addition to student viewpoints on the quality of OER themselves, there is also the issue of how students perceive instructors who use OER. Vojtech and Grissett (2017) examined this by having students read vignettes in which faculty who use OER or commercial textbooks were described. Faculty who were described as using OER were rated as more kind, more creative, and more encouraging than faculty described as using a commercial textbook.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to student viewpoints on the quality of OER themselves, there is also the issue of how students perceive instructors who use OER. Vojtech and Grissett (2017) examined this by having students read vignettes in which faculty who use OER or commercial textbooks were described. Faculty who were described as using OER were rated as more kind, more creative, and more encouraging than faculty described as using a commercial textbook.…”
Section: Resultsmentioning
confidence: 99%
“…The other category was given as a catch-all for resources missing from the given list. The given list of online resources appears fairly comprehensive as there were just 33 total responses and 12 unique resources across all courses within the other category that differed from the given resource list, with the number of students reporting the resource given in parentheses: Google or Bing search engines for general searching (12), Yahoo Answers (9),…”
Section: A Surveysmentioning
confidence: 99%
“…Adoption of OER textbooks and comparisons to print textbooks have previously been studied across disciplines [10][11][12][13][14] and within the context of introductory physics courses [15]. One may find a recent literature review of students' engagement with e-texts versus paper texts particular helpful for more information on this topic [16].…”
Section: Introductionmentioning
confidence: 99%
“…Still, in many cases the use of open textbooks saves students money; one study found that the average proprietary textbook cost was $90.61, with a wide range (Hilton III et al, 2014). Students appreciate and respond favorably to faculty members and courses in which OER are used in lieu of costly textbooks and course materials (Gabrielle & Judy, 2017). Customizability is another difference between OER and proprietary textbooks.…”
Section: Review Of Literaturementioning
confidence: 99%